Technological methods used in evaluating the balance - Ferhan Soyuer (International Journal of Spine Research - Peertechz Publications, 2020)
Balance is evaluated within the concept of coordination and is defined as the ability to maintain the body's center of gravity on the support surface. Technological methods used in the assessment of balance are robotic systems, virtual reality applications, tele-rehabilitation, web-based applications and sensor applications. In this review, we aimed to explain today's technological assessment methods and their relationship with technological rehabilitation in balance assessment. The technological method to be used in balance assessment suitability of the patient, ease of use, time saving, active participation, depending on the person's financial situation and the severity of the disease although the advantages vary, It seems that it may differ. More studies are needed for a more objective assessment of balance, designing products and using these technologies in different patient groups.